Olfactory aversive conditioning alters olfactory bulb mitral/tufted cell glomerular odor responses - Fletcher, Max L. (Frontiers in Systems Neuroscience, 2012)
The anatomical organization of receptor neuron input into the olfactory bulb (OB) allows odor information to be transformed into an odorant-specific spatial map of mitral/tufted cell glomerular activity at the upper level of the olfactory bulb. In other sensory systems, neuronal representations of stimuli can be reorganized or enhanced following learning. While the mammalian OB has been shown to undergo experience-dependent plasticity at the glomerular level, it is still unclear if similar representational change occurs within mitral/tufted cell glomerular odor representations following learning. To address this, odorant-evoked glomerular activity patterns were imaged in mice expressing a GFP-based calcium indicator (GCaMP2) in OB mitral/tufted cells. Glomerular odor responses were imaged before and after olfactory associative conditioning to aversive foot shock. Following conditioning, we found no overall reorganization of the glomerular representation. Training, however, did significantly alter the amplitudes of individual glomeruli within the representation in mice in which the odor was presented together with foot shock. Further, the specific pairing of foot shock with odor presentations lead to increased responses primarily in initially weakly activated glomeruli. Overall, these results suggest that associative conditioning can enhance the initial representation of odors within the olfactory bulb by enhancing responses to the learned odor in some glomeruli.